PENGARUH PEMBERIAN PUPUK ORGANIK LIMBAH KELAPA SAWIT TERHADAP SIFAT KIMIA TANAH SERTA PERTUMBUHAN DAN PRODUKSI TANAMAN PADI SAWAH TADAH HUJAN - PUPUT IMANIAR SHOLEHA; YULIUS B. PASOLON; NAMRIAH NAMRIAH; DARWIS DARWIS; DEDI ERAWAN; RESMAN RESMAN (Jurnal Agroteknos, 2023)
Rainfed rice fields are rice fields whose irrigation systems rely heavily on rainfall, this type of rice fields only produces in the rainy season. This rainfed rice field is categorized as marginal land lacking in nutrients. So this study aims to determine the effect of organic fertilizer from palm oil waste on the chemical properties of rainfed lowland rice, on the growth and production of rainfed lowland rice plants, as well as which fertilizer provides the best growth and production of rainfed lowland rice. This study used a completely randomized design (CRD) which consisted of one treatment, with 22% and 11% of different tangkos ashes, namely; 1) The dose of MF 22 consists of 5 levels, namely: P0 = Without treatment, P1 = 22% tangkos ash plus 6.25 g/plot organic fertilizer, P4 = 22% tangkos ash plus 124 g/plot organic fertilizer, P7 Tangkos ash = 22% added with organic fertilizer 166 g/plot, P10 = 22% tangkos ash added with organic fertilizer 207 g/plot, 2) Dosage of MF 11 consists of 5 levels, namely: P0 = Without Treatment, P1 = 11% tangkos ash added with organic fertilizer 6.25 g/plot, P4 = 11% tangkos ash added with organic fertilizer 124 g/plot, P7 = 11% tangkos ash added with organic fertilizer 166 g/plot, P10 = 11% tangkos ash added with organic fertilizer 207 g/plot. The results showed that organic fertilizer from palm oil waste was able to increase the nutrient content of organic N, P, K, C, CEC and pH in paddy soil. The application of organic fertilizer from oil palm waste had an effect on plant height, number of tillers, number of panicles, number of panicles and the weight of 1000 grains, but had no effect on the number of panicle branches, straw wet weight, straw dry weight, and the dose of organic fertilizer from palm oil waste. the best is 22% tangkos ash added with organic fertilizer 207 g/plot is better than other treatments.